2017
DOI: 10.1002/jia2.25015
|View full text |Cite
|
Sign up to set email alerts
|

Absence of neurocognitive disadvantage associated with paediatric HIV subtype A infection in children on antiretroviral therapy

Abstract: IntroductionInfection with HIV subtype A has been associated with poorer neurocognitive outcomes compared to HIV subtype D in Ugandan children not eligible for antiretroviral therapy (ART). In this study, we sought to determine whether subtype‐specific differences are also observed among children receiving ART.Materials and MethodsChildren were recruited from a clinical trial in which they were randomized to receive either lopinavir (LPV)‐ or non‐nucleoside reverse transcriptase inhibitor (NNRTI)‐ based ART (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In HIV-1 seropositive adults, prominent sex differences in the development and pattern of neurocognitive impairments have been reported (for review, Rubin et al, 2019). In PHIV, however, the effect of biological sex on chronic neurocognitive impairments remains relatively understudied with the exception of a few recent manuscripts (McLaurin et al, 2016;Bangirana et al, 2017). Given the presence of notable sex differences in neurocognitive impairments, an efficacious adjunctive therapeutic for both male and female HIV-1 seropositive individuals would be advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…In HIV-1 seropositive adults, prominent sex differences in the development and pattern of neurocognitive impairments have been reported (for review, Rubin et al, 2019). In PHIV, however, the effect of biological sex on chronic neurocognitive impairments remains relatively understudied with the exception of a few recent manuscripts (McLaurin et al, 2016;Bangirana et al, 2017). Given the presence of notable sex differences in neurocognitive impairments, an efficacious adjunctive therapeutic for both male and female HIV-1 seropositive individuals would be advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a similar proportion of children infected with subtype A and D were currently on ART. This could result in less neuropathogenic effects among these children, highlighting the importance of providing treatment to all children living with HIV [19, 36] . However, caution is warranted when interpreting the effects of HIV subtype on children's ND scores given the small sample size and the lack of statistical significance observed when comparing subtype groups.…”
Section: Discussionmentioning
confidence: 99%
“…Among school aged Ugandan HIV- infected children who had not yet received ART, HIV subtype A infection was associated with children having poorer neurocognitive performance when compared to subtype D [16] . However, Bangirana et al, reported no differences in neurocognitive outcomes when comparing Ugandan children on ART infected by HIV subtype A or D [19] .…”
mentioning
confidence: 99%
“…Thus, timing of infant HIV infection (in utero, intrapartum, postnatal), 86 maternal health status, 87 and effective ART initiation are major determinants of frequency and severity of abnormalities. Although severe CNS effects from HIV (ie, encephalopathy) are uncommon since the introduction of earlier ART, more subtle neurobehavioral abnormalities remain in some children and may be related to host, 88 viral, 89 and treatment factors. 90 There may be a critical window of opportunity when abnormalities can be prevented by early ART, 91 , 92 but the precise timing is under investigation.…”
Section: Innovations Scientific Discovery and Collaboration: Diagnomentioning
confidence: 99%